2017
DOI: 10.7554/elife.22474
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modes of SMAD2 chromatin binding and remodeling shape the transcriptional response to NODAL/Activin signaling

Abstract: NODAL/Activin signaling orchestrates key processes during embryonic development via SMAD2. How SMAD2 activates programs of gene expression that are modulated over time however, is not known. Here we delineate the sequence of events that occur from SMAD2 binding to transcriptional activation, and the mechanisms underlying them. NODAL/Activin signaling induces dramatic chromatin landscape changes, and a dynamic transcriptional network regulated by SMAD2, acting via multiple mechanisms. Crucially we have discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 66 publications
14
62
0
Order By: Relevance
“…mechanisms. In contrast, we showed that PMEPA1, whose expression is induced by TGFb or Activin signaling in many different contexts (Coda et al, 2017), is also an Activin-regulated gene in Group 3 MB. Indeed, inhibition or activation of the Activin signaling pathway modulated PMEPA1 expression accordingly.…”
Section: Activinb Induces Pmepa1 Expression and Promotes Cell Cycle Pmentioning
confidence: 55%
See 3 more Smart Citations
“…mechanisms. In contrast, we showed that PMEPA1, whose expression is induced by TGFb or Activin signaling in many different contexts (Coda et al, 2017), is also an Activin-regulated gene in Group 3 MB. Indeed, inhibition or activation of the Activin signaling pathway modulated PMEPA1 expression accordingly.…”
Section: Activinb Induces Pmepa1 Expression and Promotes Cell Cycle Pmentioning
confidence: 55%
“…We did not detect any consistent changes in MYC and OTX2 expression upon modulation of the Activin pathway, suggesting that this signaling pathway does not regulate these two genes in Group 3 tumors and promotes tumor growth through other mechanisms. In contrast, we showed that PMEPA1 , whose expression is induced by TGFβ or Activin signaling in many different contexts (Coda et al , ), is also an Activin‐regulated gene in Group 3 MB. Indeed, inhibition or activation of the Activin signaling pathway modulated PMEPA1 expression accordingly.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…To define the specific types of chromatin that Dppa4 associates with in each cell type, we examined the genome-wide association of Dppa4 with different histone modifications in P19, E14 mESC, and 3T3 cells using published and publicly available ChIP-Seq data (The ENCODE Project Consortium, 2012; Rosenbloom et al, 2012; Zullo et al, 2012; Schick et al, 2015; Zhu et al, 2012; Serandour et al, 2012; Coda et al, 2017), GSE82314. We observed strong overlap between Dppa4 binding and the active histone marks H3K4me3, H3K4me2, and H3K27ac, in all three cell types.…”
Section: Resultsmentioning
confidence: 99%